Translucency and masking ability of a translucent zirconia with different thicknesses over dark backgrounds - Renan Vaz MACHRY; Michele Mirian MAY; Ana Carolina CADORE-RODRIGUES; Letícia Borges JACQUES1; Liliana Gressler MAY (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objectives: To evaluate the translucency, contrast ratio and masking ability of a translucent zirconia with different thicknesses. Methods: Disc shaped specimens (n= 3) with 10 mm (Ø) x 1.5 mm, 1 mm and 0.7 mm (thickness) were manufactured simulating all-ceramic simplified restorations. Substrate discs (n= 2; Ø: 10 mm; thickness: 2 mm) were simulated with composite resin shades: A2 (positive control) and C4; and metal alloys: silver (Ni-Cr) and golden (Cu-Al). Optical properties of the 9 translucent zirconia specimens placed on the 3 different substrates were analyzed by a spectrophotometer. The color variation (ΔE00) between each ceramic structure over the positive control substrate (A2) and over the dark backgrounds (C4, silvery, golden) were obtained as to their ceramic masking ability and subjected to non-parametric Kruskal Wallis test (5%). The translucency parameter (TP00) and contrast ratio (CR) of the different thicknesses of the ceramic discs were also collected and analyzed by one-way ANOVA and the Tukey test (5%). Results: The translucent zirconia showed greater opacity in the thickness of 1.5 mm, although it was not statistically different between 0.7 and 1.0 mm. All dark backgrounds significantly affected the final color of the simplified restoration in all evaluated thicknesses. However, the increase in ceramic thickness showed a decrease in ΔE00 values for all substrates. Conclusion: The translucent zirconia was not able to mask the dark substrates, independent of the evaluated thickness.